2023
DOI: 10.3389/fchem.2023.1065986
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of silver nanoparticles through the Piper cubeba ethanolic extract and their enzyme inhibitory activities

Abstract: Introduction: The area of “Green Synthesis of Nano-medicine,” as compared to its synthetic counterparts, is a relatively safer research technology for various biomedical applications, including identification, therapeutic application, and prevention of pathological conditions, pain control, safety, and development of human wellness. The present study explored the synthesis and characterization of AgNPs using the ethanolic extract of Piper cubeba fruit as a reducing and stabilizing agent and its potential as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The aqueous extract from the same study contained 2.11 mg/g of total phenols . According to certain literature, each of the four ingredients’ centers of adsorption are oxygen atoms and aromatic rings. , Consequently, P.cubebaOE could be investigated as a corrosion inhibitor that is friendly to the environment. Our work examined the inhibitory effect of this extract on C-steel in 1.0 M H 2 NSO 3 H acid using a classical method (wt loss), PD, and EIS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous extract from the same study contained 2.11 mg/g of total phenols . According to certain literature, each of the four ingredients’ centers of adsorption are oxygen atoms and aromatic rings. , Consequently, P.cubebaOE could be investigated as a corrosion inhibitor that is friendly to the environment. Our work examined the inhibitory effect of this extract on C-steel in 1.0 M H 2 NSO 3 H acid using a classical method (wt loss), PD, and EIS.…”
Section: Introductionmentioning
confidence: 99%
“… 32 The aqueous extract from the same study contained 2.11 mg/g of total phenols. 33 According to certain literature, each of the four ingredients’ centers of adsorption are oxygen atoms and aromatic rings. 33 , 34 Consequently, P.cubebaOE could be investigated as a corrosion inhibitor that is friendly to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to rutin (8 ppm) and catechin (5 ppm), researchers found that the aqueous extract of piper cubeba fruits also contained gallic acid (8 ppm), caffeic acid (13 ppm), syringic acid (3 ppm), and ferulic acid (11 ppm[21]. The aqueous extract from the same study contained 2.11 mg/g of total phenols [22].In some literature, oxygen atoms, and aromatic rings are considered the centers of adsorption in the four ingredients [22,23]. As a result, (P.cubebaOE) may be studied as an environmentally friendly corrosion inhibitor.…”
Section: Introductionmentioning
confidence: 99%